Work Stress, Burnout, and Patient Satisfaction Towards Nurses Working in Medicare Hospital, Multan - Ghazanfar, Robina; Noreen, Hafsa; Sher, Nuzhat; Nouman, Adeel (Biological and Clinical Sciences Research Journal, 2025)
Nurse burnout and work-related stress are critical factors that can influence patient care quality. Understanding their impact on patient satisfaction, particularly in high-pressure settings like emergency departments, is essential for improving healthcare outcomes. Objective: To assess the association between burnout and work stress in nurses with patient satisfaction in the emergency department. Methodology: A cross-sectional study was conducted in the Emergency Department of Medicare Hospital, Multan, from December 2023 to December 2024. A total of 100 nurses working in the emergency department for at least 1 year were included in the study. Study data was collected through questionnaires. A 22-item Nursing Stress Scale was used to assess work stress through incidences in the workspace. A 16-item Maslach Burnout Inventory-General Services Scale was used to evaluate burnout in nurses. The questionnaire was divided into three sections: emotional exhaustion, cynicism, and personal effectiveness. Patient satisfaction was measured on a 12-item La Mónica-Oberst Patient Satisfaction Scale presented to emergency department patients after 1-2 days of admission. Results: No significant associations were observed between demographic and professional parameters, stress, burnout, and patient satisfaction. The mean satisfaction score was 4.71 ± 0.93, showing an adequate positive perception among patients. The mean nurse stress score was 0.99 ± 0.10, emotional exhaustion score was 2.02 ± 0.28, cynicism score was 1.49 ± 0.21, and personal effectiveness score was 5.08 ± 0.30, indicating low stress, exhaustion, and cynicism which lead to high performance. Only 5% of the nurses experienced burnout, which was associated with stress experienced at work. However, patient satisfaction was not associated with burnout or stress levels of nurses. Conclusion: Stress and burnout parameters of nurses were not significantly associated with patient satisfaction. However, further research is needed in this field.